The Cuckoo's Egg in Honneth's Hegel-Inspired Theory of Recognition: The Hobbesian Myth of Autonomy Revisited. Issue 1 (2nd January 2017) - Phillips, James
ABSTRACT: Axel Honneth reads the young Hegel as engaged in a debate with Hobbes over the social nature of the autonomous self. In the passages that are crucial for the development of Honneth's own theory of recognition the Jena manuscripts nevertheless do not mention Hobbes by name. Attributing to Hegel an advance on Hobbes's influential early modern account of individual autonomy, Honneth does not duly consider the polemical context in which Hobbes wrote. A re-examination of the polemical use to which Hobbes puts the notion of individual autonomy raises questions concerning the extent to which Honneth can straightforwardly valorise individual freedom.